Comparative Analysis of Modular Pin-Fin Heat Sink Performance: Influence of Geometric Variation on Heat Transfer Characteristics - Alfian, Devia Gahana Cindi; Silitonga, Dicky Januarizky; Ramadhan, Muhammad Al Fajri; Ridhwan, Ihsan Naufal; Utomo, Rionaldi Prasetyo; Rudiarta, I Made (International Journal of Integrated Engineering, 2024)
The advancement of digital technology in the age of Industrial Revolution 4.0 has driven other engineering sectors to keep up with the progressive demand for high-performance computing and electronics. Thermal management is one of the fields that play a crucial role in maintaining the performance of electronic devices by keeping the system temperature at an optimum level and preventing overheating. A heat dissipation device widely employed in computing and other electronic systems’ heat management is a fin-type heat sink, owing to its robust and simple design. In this work, the authors evaluated heat sinks of different pin-fin cross-sectional geometry, arranged in a staggered configuration, in terms of heat transfer characteristics under forced convection. Three basic geometries were chosen on the grounds of manufacturing easiness and market availability: circular, square, and hexagonal. All the tested geometries had approximately the same hydraulic diameter. Therefore, the results could be compared to each other. The investigation revealed that the square cross-section induced an excellent convection coefficient, hence higher heat dissipation, compared to the counterparts. The tradeoff between heat transfer performance and size-related parameters, such as surface area and material volume, is also discussed in this paper.